Odpowiedzi

  • Użytkownik Zadane
2009-12-16T13:58:09+01:00
1 .( x² + 2x + x + 2)(x+3) = x³ + 2x²+ x² + 2x + 3x² + 6x + 3x +6 = x³ + 6x² + x²+ 9x + 6
2 .(5k+n)(k-2n)-k(4k+n) = 5k² - 10kn+ kn -n- 4k²- kn= k²- 10kn - n
3. (4y+3)(y-2)-2y(4-2y) = 4y²+8y + 3y - 6 - 8y + 4y² = 8y² + 3y - 6
2009-12-16T14:02:37+01:00
[x+1]*[x+2]*[x+3]=[x²+2x+x+2]*[x+3]=x³+3x²+2x²+6x+x²+3x+2x+6=x³+6x²+11x+6


[5k+n][k-2n]-k[4k+n]=5k²-10kn+kn-2n²-4k²-kn=k²-2n²-13kn


[4y+3][y-2]-2y[4-2y]=4y²-8y+3y-6-8y+4y²=8y²-13y-6

-[3c-2][c-1]-c[c-2]=-[3c²-3c-2c+2]-c²+2c=-3c²+3c+2c-2-c²+2c=-4c²+7c-2


5x²[x²+1]-[x²-2][x²+3]=5x⁴+5x²-[x⁴+3x²-2x²-6=5x⁴+5x²-x⁴-3x²+2x²+6=4x⁴+10x²+6